STUDI TEBAL PERKERASAN JALAN MENGGUNAKAN METODE BINA MARGA 2013 DAN DRAINASE JALAN - Fanditya Dwi Purangga; Rofi Budi Hamduwibawa; Taufan Abadi (Universitas Muhammadiyah Jember, 2020)
Flexible pavement is one of the pavements that generally uses a mixture of materials originating as a surface layer and a grained material as the layer underneath. So that the pavement layer has flexibility / flexibility that can create vehicle comfort when passing on it. It is necessary to conduct a more intensive study in its application and also take into account economically, according tolocal conditions, level of need, implementation capacity and other technical requirements, so that the planned road construction is optimal. Drainage which comes from English (drainage) means to drain, drain, remove, or divert water. In the field of civil engineering, in general, drainage can be defined as an action to reduce excess water, which comes from rain, seepage, or excess irrigationwater from an area / land, so that the function of the area / land is not disturbed. Drainage is also defined as an effort to control groundwater quality in terms of sanitation. So, it concerns not only surface water but also groundwater. Based on the data that has been processed using the Bina Marga method in 2013, it can be seen that there are several things that experience significantdifferences. It is known that ESA 20 years = 3,922,232 uses a pavement thickness of HRS WC 3 cm, HRS Base 3.5 cm, LPA class A 37.5 cm while for the duct dimensions the values of b are 0.6 m and h 0.6 m.